Effects of short-term oral administration of propranolol on tear secretion in clinically normal dogs - Ghaffari, Masoud Selk (Canadian Veterinary Medical Association, 2011)
This study evaluated the effects of short-term oral administration of propranolol on tear secretion in 15 clinically normal crossbreed dogs. The treatment group (n = 8) received propranolol (2 mg/kg q8h) orally for 7 days. The control group (n = 7) received placebo during the study. Schirmer I tear tests were performed on both eyes 1 d prior to drug administration (T(0)), at 1 (T(1)), 3 (T(3)), and 7 (T(7)) days of treatment. Tear production in dogs, measured by STT, was not significantly reduced in both groups.